The ErbB family and androgen receptor signaling are targets of Celecoxib in prostate cancer. (1st August 2017) - Brizzolara, Antonella; Benelli, Roberto; Venè, Roberta; Barboro, Paola; Poggi, Alessandro; Tosetti, Francesca; Ferrari, Nicoletta
Abstract: Inflammation plays a central role in prostate cancer (PCa) development through significant crosstalk between the COX-2-ErbB family receptor network and androgen receptor (AR)-EGFR signaling pathways. The purpose of this work was to determine the ability of the COX-2 inhibitor Celecoxib to modulate the EGFR-AR signaling pathway in androgen-dependent PCa cells and to provide a rationale for its beneficial use in chemopreventive strategies. Functional studies of Celecoxib activity were performed on LNCaP prostate cancer cells. Western blotting, gene expression analysis, dual-luciferase reporter assay and ELISA were applied to assess the Celecoxib mechanisms of action. We found that Celecoxib, through EGF and amphiregulin (AREG) induction, caused EGFR and ErbB2 activation and consequent degradation associated with the inhibition of androgenic signaling. By upregulating the E3 ubiquitin ligase Nrdp1, Celecoxib also efficiently downregulated ErbB3, which is strongly implicated in castration-resistant prostate cancer. Lastly, Celecoxib directly regulated AR transcription and translation independent of ErbB activation by downregulating the RNA binding protein heterogeneous nuclear ribonucleoprotein K (hnRNP K). The simultaneous suppression of ErbB kinases and androgen signaling by Celecoxib represents a novel strategy to interrupt the vicious cycle of AR/ErbB cross-talk with the primary purpose of undermining their resilient signaling in prostate cancer progression. Our data provide important premises for the chemopreventive use of Celecoxib in the clinical management of prostate cancer. Highlights: In PCa AR induces EGFR which in turn activates AR in the absence of androgen. Celecoxib coherently downregulates ErbB receptors and AR in PCa while sparing normal cells. Celecoxib also reduces hnRNP K, a regulator of AR translation. Blocking EGFR and AR at the same time is an attractive strategy for PCa chemoprevention.